2022
DOI: 10.3390/antibiotics11050596
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Multidrug-Resistant Hypervirulent (Hypermucoviscous) Klebsiella pneumoniae Strain Lacking the Hypermucoviscous Regulators (rmpA/rmpA2)

Abstract: Hypervirulent K. pneumoniae (hvKP) strains possess distinct characteristics such as hypermucoviscosity, unique serotypes, and virulence factors associated with high pathogenicity. To better understand the genomic characteristics and virulence profile of the isolated hvKP strain, genomic data were compared to the genomes of the hypervirulent and typical K. pneumoniae strains. The K. pneumoniae strain was isolated from a patient with a recurrent urinary tract infection, and then the string test was used for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…However, the details of antibiotic susceptibility testing results are lacking in patients with EKE. Amidst growing concern over the emergence of multidrug-resistant (MDR) bacteria, selecting appropriate antibiotics for infection treatment has become a critical issue [ 14 , 15 ]. Common variants of MDR K. pneumoniae include extended-spectrum β-lactamase (ESBL)-producing and carbapenemase-producing K. pneumoniae [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the details of antibiotic susceptibility testing results are lacking in patients with EKE. Amidst growing concern over the emergence of multidrug-resistant (MDR) bacteria, selecting appropriate antibiotics for infection treatment has become a critical issue [ 14 , 15 ]. Common variants of MDR K. pneumoniae include extended-spectrum β-lactamase (ESBL)-producing and carbapenemase-producing K. pneumoniae [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amidst growing concern over the emergence of multidrug-resistant (MDR) bacteria, selecting appropriate antibiotics for infection treatment has become a critical issue [ 14 , 15 ]. Common variants of MDR K. pneumoniae include extended-spectrum β-lactamase (ESBL)-producing and carbapenemase-producing K. pneumoniae [ 14 , 15 , 16 ]. Although most isolates causing ocular infections are not caused by MDR bacteria, antibiotic susceptibility testing may reveal antibiotic susceptibility and resistance trends.…”
Section: Introductionmentioning
confidence: 99%
“…KP has evolved and become resistant to third-generation cephalosporins and carbapenems, which has led to narrow treatment options for MDR KP, and in some settings, entirely removed [ 17 ]. However, there is a continuous surge in the prevalence of MDR KP strains; hypermucoviscous and hypervirulent KP strains have also been acknowledged and described [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This collection also gathers papers on antibiotic resistance of some of the major emerging infections pathogens such as Mycobacteroides abscessus [ 3 ], Klebsiella pneumoniae [ 4 , 5 ], Salmonella sp. [ 6 , 7 ], Francisella tularensis [ 8 ], Acinetobacter baumannii [ 9 , 10 ], or Pseudomonas aeruginosa [ 11 ] and other human pathogens such as Neisseria gonorrhoea [ 12 ], Staphylococcus aureus [ 13 ], or Escherichia coli [ 14 ].…”
mentioning
confidence: 99%
“…Altayb et al studied and isolated a K. pneumoniae isolate from a patient with recurrent urinary tract infection, identified as hypermucoviscent, type 2 (K2) capsular polysaccharide, ST14, and multidrug-resistant. The authors performed genomic analysis and demonstrated that it harbors four plasmids, several virulence factors, and antibiotic resistance encoding genes, which are worth studying in more detail [ 5 ].…”
mentioning
confidence: 99%